Analysis of the involvement of cytokines in allergy and breast cancer association - Kowalczewska, Małgorzata E.; Brożyna, Anna; Jóźwicki, Wojciech; Pławski, Krzysztof; Przybyszewski, Michał; Wrotek, Sylwia; Bartuzi, Zbigniew; Kozak, Wiesław (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study: The existence of a correlation between allergy disorders and cancer diseases has been confirmed by several epidemiological studies. Although the molecular mechanism involved in this phenomenon remains unknown, there are data indicating that certain cytokines, engaged in allergic processes, have antineoplastic activities. The aim of the present study was to explore the association between advanced breast cancer and allergic state on the molecular level. Material and methods : We determined and compared the mRNA and protein expression of interleukin-1β (IL-1β), IL-4, IL-6, and interferon-γ (IFN-γ), cytokines known for antitumor properties, in the blood of advanced breast cancer patients and individuals with allergic diseases related to type 2 response. In addition, we performed an in vitro assay of reactivity of peripheral blood mononuclear cells after exogenous antigen stimulation. As a preliminary to molecular analysis we conducted a questionnaire study concerning the incidence of allergy among breast cancer patients and healthy subjects without malignancy. Results : The results of the survey study revealed a negative relation between breast cancer and allergy prevalence. Subsequent molecular analysis, however, did not show statistically significant differences in cytokines mRNA and protein expression levels between allergic patients and those with malignancy. The in vitro reactivity test also did not reveal marked differences between IL-1β, IL-4 and IL-6 production after PBMC triggering with exogenous antigen. Conclusions : We concluded that the studied cytokines (IL-1β, IL-4, IL-6, and IFN-γ) are not engaged in breast cancer-allergy negative relation.